Creativity-Focused Mindfulness for Student Well-Being. (1st October 2020) - Henriksen, Danah; Shack, Kyle
Abstract: Taking a whole-child approach to schooling, the authors address how creativity and mindfulness are connected and suggest practical ways that teachers can integrate them into the curriculum.